Amphibia, Anura, Hylidae, Dendropsophus anceps: distribution extension in state of São Paulo, Brazil - Daniel Rolim; Fábio Maffei; Renata Sene; Cesar Medolago; Tiago Vernini; Flávio Ubaid; Jorge Jim (Check List, 2008)
None